A pH-responsive PVDF membrane with superwetting properties for the separation of oil and water. Issue 30 (3rd March 2015) - Xiang, Yanhui; Shen, Jianhui; Wang, Yunze; Liu, Fu; Xue, Lixin
Abstract : The wettability and flow channel of PDMAEMA modified PVDF membrane is controllable by media pH. Abstract : Responsive materials with surfaces that have controllable oil wettability under water offer considerable potential in advanced applications. We have developed an economical and convenient method for constructing a superwetting polyvinylidene fluoride (PVDF) membrane, giving super-hydrophobicity under oil and super-oleophobicity under water. The membrane has been achieved by incorporating pH-responsive N, N -dimethylaminoethylmethacrylate (DMAEMA) hydrogels into PVDF using a combination of in situ polymerization and conventional phase separation. In pure or acidic water the poly-DMAEMA chains modify wettability by the protonation or deprotonation of their tertiary amine side-groups, affecting the wettability of the membrane under water. In addition, this responsive membrane has been utilized for the separation of surfactant-stabilized water-in-oil and oil-in-water emulsions. High flux and separation efficiency can be obtained, together with excellent antifouling properties, suggesting that the membranes will find wide application in the separation of oil and water systems.